A comprehensive evaluation framework to evaluate energy management strategies of fuel cell electric vehicles. (1st December 2018) - Song, Ke; Chen, Huan; Wen, Peimin; Zhang, Tao; Zhang, Boqiang; Zhang, Tong
Abstract: The fuel consumption and degradation of electric vehicle fuel cells are strongly affected by their energy management strategy (EMS). This paper proposes a comprehensive framework to evaluate the effects of different energy management strategies. The proposed approach consists of three EMS priorities. The first priority is fuel cell durability. In this case, performance degradation of the fuel cell stack is evaluated based on the degradation of fuel cell key components, which are tested under four unfavorable operating conditions with the help of the fuzzy comprehensive evaluation theory. Fuel economy is the second evaluation priority and is based on a dynamic programming algorithm designed to obtain global optimal driving mileage as a benchmark. The third EMS priority is to obtain a synthesis of weighted fuel cell durability and fuel economy evaluation for a comprehensive final check. A typical rule-based power-following EMS and a wavelet-transform-based EMS are designed in this paper to validate the proposed EMS evaluation approach based on a fuel cell electric vehicle model. The simulation results show that the introduced comprehensive evaluation framework can effectively assess different EMSs for fuel cell electric vehicles synthetically and quantitatively and provide an optimization guide.